Anuario 1996 de normas ASTM. - American Society for Testing and Materials (Philadelphia : ASTM, 1996)
Incluye normas de tuberias y accesorios de acero.
v.2 (Non ferrous metal Products) Tomo 1: Copper and Alloys; Tomo 2: Aluminium and magnesium Alloys -- v.3 (Metals test Methods and Analytical Procedures) tomo1 Metals-Mechanical testing: elevated and low-temperatureTest,Metalography; Tomo 3: Nondestructive Testing
Keywords: NORMAS -- PUBLICACIONES SERIADAS; PRODUCTOS DE ACERO; TUBERIAS DE ACERO; ACCESORIOS DE ACERO; ACEROS INOXIDABLES